Pelatihan Penyusunan Media Pembelajaran IPS Interaktif Berbasis Digital Bagi Guru Sekolah Dasar - Treesly Y.N Adoe; Vera R Bulu; Markus Sampe; Taty R. Koroh (Prodi PGSD Unsultra, 2025)
The development of digital technology in education requires teachers to develop interactive, engaging, and learner-centered instructional media. However, some elementary school teachers still face challenges in designing and utilizing digital learning media, particularly in Social Studies (IPS) instruction. This community service program aimed to improve teachers’ understanding and skills in developing interactive digital-based Social Studies learning media. The program was conducted at SD Inpres Oeba 2 using a participatory approach through several stages, including planning, training implementation, media development practice, mentoring, and evaluation. The activities were carried out through material presentation, discussions, demonstrations, case studies, hands-on practice, consultations, and reviews of learning media developed by the teachers. The results showed that the training and mentoring activities contributed positively to improving teachers’ abilities to design digital-based Social Studies learning media. Teachers were able to develop media that integrated text, images, videos, digital resources, and interactive activities according to learning objectives and students’ characteristics. The program also increased teachers’ participation and confidence in utilizing digital technology to support Social Studies learning. The developed media have the potential to support the presentation of learning materials in a more systematic, concrete, engaging, and contextual manner. Therefore, practice-based training and mentoring can serve as relevant strategies for strengthening the digital competence of elementary school teachers. Further training and continuous mentoring are recommended to ensure the sustainable improvement and implementation of teachers’ skills in developing digital learning media in classroom instruction.